Current Study on Antidepresan Activity of Chocolate Drink in Pregnan Woman in Jombang, Indonesia - Farach Khanifah; Nining Mustika Ningrum; Yasmin Asih Scheiber (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Pregnancy is a natural and physiological process that occurs in every woman. But often pregnant women experience anxiety and worry during pregnancy, this is a normal thing to happen during pregnancy. Symptoms of anxiety during pregnancy vary including anxiety, worry, and anxiety that are difficulty to control, irritability, irritability, difficulty concentrating, body muscles being painful and tense, lack of energy, disturbed sleep patterns, and disturbed rest patterns. Such anxiety can occur during pregnancy in both the I Trimester, II Trimester, and III Trimester. Although anxiety is normal in pregnancy, anxiety symptoms can occur on an ongoing basis if not addressed. The purpose of this study was to analyze the effectiveness of giving chocolate drinks as a complementary therapy to antidepressants in pregnancy. This type of research is quantitative analytics using a Quasi-Experimental research design with one group pre-post test design method using one treatment group. Free variables: Administration of chocolate drinks and bound variables: complementary therapy of antidepressants in pregnancy. The sample in this study was pregnant women who experienced anxiety in pregnancy both mild, moderate, severe, and even panic which matched the inclusion criteria of 124 people. Sampling using purposive sampling techniques. Instrument: HARS (Hamilton Anxiety Rating Scale) and Observation sheet. Data analysis using the Wilcoxon Test. The results showed that the anxiety of pregnant women before being given chocolate drinks was mostly 62.9% experienced mild anxiety, 35.5% experienced moderate anxiety and 1.6% experienced severe anxiety and after being given chocolate drink therapy more than half of the respondents namely 55.6% had no anxiety, 29% had mild anxiety, 15.4% had moderate anxiety and none of the respondents experienced severe anxiety and panic. This study concludes that giving chocolate drinks has activity as an antidepressant in pregnant women. It is hoped that all healthcare providers for pregnant women can recommend complementary therapies with herbal ingredients, especially chocolate as a therapy for reducing anxiety (antidepressants) during pregnancy. So that the benefits of this study can provide a solution for pregnant women who are depressed to use chocolate drinks as an alternative therapy to calm the depressive state.